Epidemiology of female infertility in Sonepat district of Haryana: a community based cross-sectional study - Kataria, Deepika; Rani, Babita; Punia, Anita; Jha, S. K.; Narendran, M.; Singh , Jagmohan (International Journal Of Community Medicine And Public Health, 2023)
Background: Infertility is a global reproductive health problem and the prevalence rate increased by 0.37% per year for females. There are many such risk factors which are avoidable. Thus the purpose of the study is to identify and quantify the burden of infertility and associated risk factors for infertility. Methods: This observational community based cross-sectional study was conducted among 444 reproductive age group (18-49 years) women residing in district Sonepat, from August 2021 to May 2022. Simple random sampling technique was used to select the study subjects. The categorical data were analyzed statistically using Chi-Square test and Odds ratio with 95% confidence interval. Continuous variables were analyzed using independent t-test. Results: Out of 444 study population majority of women were fertile (88.7%), while 6.3% of women were secondary infertile and 5% women were primary infertile. Most women were aged between 30-39 years. The difference of occurrence of infertility in relation to time since marriage, male age at marriage, number of family members, thyroid, PCOD, tuberculosis and height were statistically significant. Conclusions: Almost all the factors came out to be responsible for infertility were modifiable. Awareness generation and provision of infertility care services at primary health care facilities will be of use in addressing infertility in Haryana.